Ungendering Europe: critical engagements with key objects in feminism. Issue 7 (3rd July 2018) - Liinason, Mia; Alm, Erika
Abstract: This introduction presents the points of departure for the themed section 'Ungendering Europe: Critical Engagements with Key Objects in Feminism' and introduces the eight articles included in the collection.